Point-of-care Ultrasonography in Critically Ill Patients - Shrestha, GS (Kathmandu University Medical Journal, 2015)
Point-of-care ultrasonography has been used frequently by the physicians involved in managing critically ill patients. It allows direct visualization of pathology or abnormal physiological state at the bed side. The examination may be safely and effectively repeated as needed to follow the evolution of illness and the response to therapy. It is helpful to guide the therapy in patients with undifferentiated shock and for bedside diagnosis of common pathological conditions in acute care setting. It can facilitate common bedside procedures and interventions. Kathmandu University Medical Journal Vol.13(1) 2015; 83-87